Combating Corruption in Yudhoyono’s Indonesia: An Insider’s Perspective1 - Indrayana, Denny (Komisi Pemberantasan Korupsi, 2017)
This paper shares my experiences in combating corruption under President Susilo Bambang Yudhoyono’s (SBY) administration from 2004 to 2014. In particular, I want to give you my inside story as President SBY’s Special Advisor for Legal Affairs from 2008 to 2009; his Special Advisor for Legal Affairs, Human Rights, and Anti-Corruption from 2009 to 2011; and his Deputy Minister for Law and Human Rights from 2011 to 2014. I hope my experience of six years in government that I will share with you tonight may be of some use in building a better understanding of how difficult is to combat corruption, even for the strongest authority in the country, the President.